Web-oriented software for expert assessment questionnaire method - O. O. Zhytskyy; Yu. V. Tryus (Academy of Cognitive and Natural Sciences, 2015)
The aim of work is to create web-oriented software for expert assessment of questionnaire method. The objective of the study is to analyze the advantages and disadvantages methods of questionnaire, analysis of existing software for expert assessment, design and creation of web-oriented software for expert assessment of questionnaire method, which would be accessible to the Internet users for expert analysis of real problems and issues in business and education. The object of study is the methods and software for expert assessment. The subject of the study is web-oriented software for expert assessment of questionnaire method. The research results can be used for expert analysis of real problems and issues in business and education, and will be useful to students of universites, studing the models and methods of decision making.